Factors that affecting Malaysian housing price index / Ali Adnan Mansor - Mansor, Ali Adnan (Faculty of Business and Management, 2020)
Housing prices had became main highlighted issue in Malaysia recently. It was as regards to the rising of housing prices which causes worrisome to the Malaysian. This study is an effort to investigate the determinants of housing prices that focusing on Malaysia case from the year 2010 until 2018. There are four determinants that had been listed which are Gross Domestic Product (GDP), Population rate (POP), Unemployment Rate (UNMP) and also Currency Exchange (EXC) as independent variables meanwhile House Price Index (HPI) as dependent variable. This study using secondary data of each variables from the year 2010 to 2018 on quarterly basis. This study used statistical tool which is EViews9 software for data analysis purposes. The results had portrays all the determinants which are GDP, POP, UNMP and EXC are significant towards HPI. Thus, this study are benefit to the researcher, public as well as investors in order to be informed about trend of housing prices in Malaysia.